Vestibular Extremely Low‐Frequency Magnetic and Electric Stimulation Effects on Human Subjective Visual Vertical Perception. Issue 6 (8th July 2022) - Bouisset, Nicolas; Villard, Sébastien; Legros, Alexandre
Abstract : Electric fields from both extremely low‐frequency magnetic fields (ELF‐MF) and alternating current (AC) stimulations impact human neurophysiology. As the retinal photoreceptors, vestibular hair cells are graded potential cells and are sensitive to electric fields. Electrophosphene and magnetophosphene literature suggests different impacts of AC and ELF‐MF on the vestibular hair cells. Furthermore, while AC modulates the vestibular system more globally, lateral ELF‐MF stimulations could be more utricular specific. Therefore, to further address the impact of ELF‐MF‐induced electric fields on the human vestibular system and the potential differences with AC stimulations, we investigated the effects of both stimulation modalities on the perception of verticality using a subjective visual vertical (SVV) paradigm. For similar levels of SVV precision, the ELF‐MF condition required more time to adjust SVV, and SVV variability was higher with ELF‐MF than with AC vestibular‐specific stimulations. Yet, the differences between AC and ELF‐MF stimulations were small. Overall, this study highlights small differences between AC and ELF‐MF vestibular stimulations, underlines a potential utricular contribution, and has implications for international exposure guidelines and standards. © 2022 Bioelectromagnetics Society.